DETERMINAN NILAI PERUSAHAAN - Septiani, Indah; Syahzuni, Barlia Annis (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2025)
The objective of the research is to study and provide evidence about the influence of profitability, leverage, firm size, stock return, and firm growth on the value of firms in the healthcare sector active on the Indonesian Stock Exchange. (BEI). Research is carried out using a causality approach to understand the cause-and-effect relationship between two or more variables. Apply panel data regression with samples of 44 observation data consisting of a combination of cross-section data from 11 companies with time-series data over four years from 2020 to 2023. This research was done using statistical analysis tools. The Fixed Effect Model was chosen through the Chow test and the Hausman test and has met the classical assumption test. The data showed that partial profitability, leverage, firm size, and firm growth did not significantly affect the firm’s value. As for the variable stock return, it can influence the value of firms positively and significantly.